Hubungan antara Skor Beighton dan Usia Berjalan pada Anak - Lavenia Kurniawati; Indrayuni Lukitra Wardhani; Nur Rochmah; Sulistiawati Sulistiawati (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2021)
Introduction: Studies showed that the condition of joint hypermobility is quite common in children. In general, joint hypermobility asses through the Beighton score method. The objective of this research was to investigate the relationship between beighton score and walking age in children.Method: This research was conducted at a kindergarten in Surabaya using an observational analytic research type and a cross-sectional design. Data collected through interviews and physical examinations. A joint hypermobility examination performed using the Beighton score criteria. Meanwhile data was analyzed using the crosstabulation and Spearman test.Result: It was found that 84% of children had ≥4/9 score on the Beighton score and there were 92% with positive Beighton score in the knee joint. In this study, as many as 20 children experienced the first independent walks over 18 months when 18 of them who has Beighton score ≥4 points. However, there is no correlation found on the Beighton score and the walking age [sig. (2-tailed) = 0.053].Conclusion: Children who have ≥4 points of Beighton score are mostly found in this study. The relationship between the Beighton score and walking age was not statistically significant.